Keutamaan Gereja dalam Menghadapi Tantangan dan Mempertahankan Toleransi dalam Berbagai Agama-Agama di Indonesia - Erlangga Saputra; Malik Bambangan (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
By writing scientific papers, he talked about how the virtue of the Christian Church in the midst of the majority and living became an example in encountering problems and introducing interfaith tolerance in Indonesia. As a country with strong religious traditions, Indonesia has challenges in creating harmonious relationships between all communities. In this writing, I am also trying to write that with the education of teaching love, the Christian church has the potential to become an agent of reconciliation in a pluralistic society. Christian teachings on selfless love, forgiveness, and acceptance of discrimination provide opportunities for people to actively participate in interfaith dialogue. However, the Church also addresses theological and social issues as absolute.